A strategic plan for Greenwave Development Multi-Purpose Cooperative (GDMPC) - Delfino, Annalou B. (School of Management, University of the Philippines Mindanao, 2010)
The three-year plan of Greenwave Development Multi-Purpose Cooperative (GDMPC) is about to end. The current board of directors would like to set the cooperative?s strategic plan in the next five years in relation to the evaluation of its internal and external environment. This strategic plan was based on an analysis of the cooperative?s performance the past five years in the main functional areas of human resource, marketing, operations and finance as well as an assessment of its external environment using the Socio-Cultural, Technological, Economic, Environmental, and Political (STEEP) Analysis. The strategic management framework of Fred David was used to set the long-term direction of the cooperative in line with its Vision, Mission and Goal. In determining the strategic options of the cooperative, SWOT (Strength, Weaknesses, Opportunities and Threats) analysis was employed in the study. And finally, QSPM (Quantitative Strategic Plan Matrix) was used in choosing which among the strategic options of the cooperative are to be undertaken. Results from the QSPM showed the strategic options of the cooperative that were narrowed down into doable options. Market Penetration is the first strategy that GDMPC will work on. With the increasing demand and awareness of people in the community to the effectiveness and cheapness of herbal products, it is also right for the cooperative to match this trend. Educating the people in the community through the conduct of seminars would likely increase the volume of users of these herbal products which leads also to the increase in sales of the cooperative. Product and service development is next in the set of doable strategies of the cooperative. Existing products of the cooperative such as the extending of loans to its members and the services offered such as the consultation to the resident doctor and the acupuncture and acupressure services must be enhanced and developed to add income to the cooperative. And lastly, GDMPC has to improve and standardize the way they do things. Standardization would include computerization of all reports for proper monitoring and control. The cooperative should also come up of a personnel handbook that will serve as the standard basis of the cooperative to hire people, and to structure their benefits. Training their personnel is also part of the standardization in line with its computerization plan. The mission, vision and goals of GDMPC were revisited and in consideration of its internal and external factors, the five (5) year (2010-2015) implementing program of the cooperative was made as a result of the proposed strategies.